Sālimīyah Sect and its Doctrinal Opinions on the Divine Self in the Light of Islamic Doctrine - Ahmad, Eisa Rabeeh (Arab Journal for Sciences and Research Publishing, 2021)
It is widely known that there are Islamic ideological sects and groups whose doctrinal opinions still exist to date, such as Asha’yrah, Maturidis, and Hanbalis, while we find other ideological groups that do not exist in our modern times. Chief among these ideological sects and groups is Sālimīyah sect, that belongs to its founder, Abul-Hassan Al-Basry Ahmad bin Mohammad bin Salem, who died in (297) AH / (909) AD. Sālimīyah sect is an Islamic ideological group that emerged in the middle of the third century AH / mid-tenth century AD. In fact, one of the most problematic issues of this study is that there are no ideological books for Sālimīyah sect available in our time. Few scholars mentioned the ideological views of Sālimīyah sect and we could hardly find any other academic studies that have considered these views. What really distinguishes this study is its ability to scrutinize for the first time the emergence of Sālimīyah sect from a historical point of view. Moreover, this research studies Sālimīyah sect's ideological views related to the Divine Self in particular. The scientific approaches used in the study are the extrapolative approach, the analytical approach and the comparative approach.
Keywords: Sālimīyah sect; Abul-Hassan Al-Basry; Embodiment; Islamic Doctrine; Divine Self